The International Network of Obstetric Survey Systems study of uterine rupture: a descriptive multi-country population-based study - Vandenberghe, G; Bloemenkamp, K; Berlage, S; Colmorn, L; Deneux-Tharaux, C; Gissler, M; Knight, M; Langhoff-Roos, J; Lindqvist, P; Oberaigner, W; Van Roosmalen, J; Zwart, J; et al. (Wiley, 2018)
Objective International comparison of complete uterine rupture. Design Descriptive multi‐country population‐based study. Setting International. Population International Network of Obstetric Survey Systems (INOSS). Methods We merged individual data, collected prospectively in nine population‐based studies, of women with complete uterine rupture, defined as complete disruption of the uterine muscle and the uterine serosa, regardless of symptoms and rupture of fetal membranes. Main outcome measures Prevalence of complete uterine rupture, regional variation and correlation with rates of caesarean section (CS) and trial of labour after CS (TOLAC). Severe maternal and perinatal morbidity and mortality. Results We identified 864 complete uterine ruptures in 2 625 017 deliveries. Overall prevalence was 3.3 (95% CI 3.1–3.5) per 10 000 deliveries, 22 (95% CI 21–24) in women with and 0.6 (95% CI 0.5–0.7) in women without previous CS. Prevalence in women with previous CS was negatively correlated with previous CS rate (ρ = −0.917) and positively correlated with TOLAC rate of the background population (ρ = 0.600). Uterine rupture resulted in peripartum hysterectomy in 87 of 864 women (10%, 95% CI 8–12%) and in a perinatal death in 116 of 874 infants (13.3%, 95% CI 11.2–15.7) whose mother had uterine rupture. Overall rate of neonatal asphyxia was 28% in neonates who survived. Conclusions Higher prevalence of complete uterine ruptures per TOLAC was observed in countries with low previous CS and high TOLAC rates. Rates of hysterectomy and perinatal death are about 10% following complete uterine rupture, but in women undergoing TOLAC the rates are extremely low (only 2.2 and 3.2 per 10 000 TOLACs, respectively.) Tweetable abstract Prevalence of complete uterine rupture is higher in countries with low previous CS and high TOLAC rates.